Diabetic Retinopathy: Clinical Features, Risk Factors, and Treatment Options - Mishra, Sudhanshu; Vishwakarma, Pratik K.; Tripathi, Mridani; Ojha, Smriti; Tripathi, Shivendra Mani (Current Diabetes Reviews, 2024)
Diabetic retinopathy is a common complication of diabetes that affects the eyes and can lead to severe vision loss or blindness if left untreated. Chronic hyperglycemia destroys the blood vessels in the retina, resulting in diabetic retinopathy. The damage can lead to leakage of fluid and blood into the retina, causing edema, hemorrhages, and ischemia. A thorough evaluation by an ophthalmologist is necessary to determine the most appropriate course of treatment for each patient with diabetic retinopathy. The article discusses various surgical treatment options for diabetic retinopathy, including vitrectomy, scleral buckling, epiretinal membrane peeling, retinal detachment repair, and the risk factors of diabetic retinopathy. These surgical techniques can help to address the underlying causes of vision loss and prevent further complications from developing or worsening. To avoid complications and maintain vision, this review emphasizes the significance of early detection and treatment of diabetic retinopathy. Patients with diabetic retinopathy can improve their eyesight and quality of life with the help of some surgical treatments. The article also highlights some case studies in the field of diabetic retinopathy.
Keywords: Glucose